Smartphone addiction and its association with upper body musculoskeletal symptoms among university students classified by age and gender - Hanphitakphong, Panida (J Phys Ther Sci, 2021)
[Purpose] The purposes of this study were to: 1) survey smartphone addiction among university students, 2) survey the prevalence of upper body musculoskeletal symptoms in relation to the respondents’ sitting posture, and 3) determine the association between smartphone addiction and upper body musculoskeletal symptoms, classified by age and gender. [Participants and Methods] Two self-report questionnaires were employed to collect data from 2,645 university students in Chiang Mai, Thailand. [Results] Of 2,027 respondents (860 males and 1,167 females), the participants’ ages ranged from 18 to 26 years with a mean age of 20.5 ± 1.38 years. The prevalence of smartphone addiction and upper body musculoskeletal symptoms among participants were 15.9% and 30%, respectively. Overall, the mean value of pain severity was 3.66 ± 1.67 out of 10 on the visual analog scale. Multivariate logistic regression analysis revealed that smartphone addiction (OR=6.05, 95% CI: 4.68–7.84), was significantly associated with upper-body musculoskeletal symptoms when adjusted by age and gender. [Conclusion] The prevalence of upper body musculoskeletal symptoms was relatively high, especially for female smartphone users and students aged over 20 years. These results suggest that smartphone addiction may be a potential risk factor for upper body musculoskeletal symptoms in university students.